Size, layout and tendon profile optimization of prestressed steel trusses using Jaya algorithm. (June 2022) - Aydın, Zekeriya
Abstract: Depending on the increasing raw material costs in the construction area, it is becoming more and more significant to design the structures using minimum materials. For steel systems, where raw material prices are relatively higher than reinforced concrete structures, prestressing is one of the factors that can reduce the cost. Therefore, this study aims to cost optimization of prestressed steel trusses, considering the size and shape variables, simultaneously. It is assumed in the study that the prestressing force is applied via a tendon settled under the bottom chord and shaped with deviators. The cross-sections of the truss elements and deviators are size variables; on the other hand, the layout of the truss beam and the profile of the prestressing tendon are the shape variables. Discrete and continuous values are preferred for the size and shape variables, respectively. Strength, slenderness, and displacement are considered as the constraints in the design of prestressed steel trusses, depending on the different prestress loss conditions. The Jaya, a popular metaheuristic algorithm, is used for the optimization procedure. As numerical examples, the optimization of trusses with different spans and shapes is conducted. The results achieved are compared with those of the non-prestressed trusses and the results in the literature. It is observed that the prestressing, especially thanks to shape variables used, provides a considerable cost saving in the optimum design of steel trusses.